EVALUATION OF PHOTODYNAMIC THERAPY FOR SKIN CANCER - V. V. Gorokhov (Креативная хирургия и онкология)
TThis article presents the results of treatment of skin cancer by photodynamic therapy. The aim of this work was to investigate the efficacy of treatment for skin cancer of different locations in anatomically difficult areas and multiple primary and recurrent forms. Tumor complete regression was achieved in 88,6% of cases. Results of treatment of basal cell and squamous cell carcinoma were similar in the number of cases of complete regression and partial regression of lesions. The treatment of primary tumors anatomically difficult areas of complete response was achieved in 81,3 % of patients, and we avoided surgery.